Diversity, knowledge clusters, and job placement: Graduate economics teaching of core microeconomics. Issue 3 (3rd July 2017) - Campbell, Arthur; Feinstein, Jonathan S.; Hong, Soonwook; Qian, Sharon; Williams, Trevor C.
ABSTRACT: The authors present an empirical analysis of what is taught in core micro-economics at a set of top U.S. doctoral economics programs. Their aim is to evaluate the diversity across programs and assess whether there are distinct "schools of thought" in graduate economics education. Their empirical findings reveal substantial, in fact, surprising diversity in what is taught. Application of a clustering algorithm results in programs clustering into two main "schools of thought." The authors also specify an econometric model of job placement. Their job placement results indicate that candidates are more likely to be hired at schools in the same cluster as their home program, even after controlling for other factors. The results inform debates about graduate education and the relevance of a "common core" curriculum.